2006
DOI: 10.1677/jme.1.01936
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specificity of transforming growth factor-β response is dictated by receptor bioavailability

Abstract: Members of the transforming growth factor-(TGF ) family control diverse cellular responses including differentiation, proliferation, controlled cell death and migration. The response of a cell to an individual ligand is highly restricted yet the signaling pathways for TGF , activin and bone morphogenic proteins share a limited number of receptors and activate similar intracellular cytoplasmic co-regulators, Smads. A central question in the study of this family of ligands is how cells titrate and integrate each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…We did not examine ALK6 here because an earlier report indicated that it was not expressed in LbT2 cells or adult mouse pituitary (Otsuka & Shimasaki 2002). However, more recent work shows that this receptor is in fact expressed (Suszko & Woodruff 2006), and we confirm this observation here. Given that ALK6 is more similar to ALK3 than ALK2, one would predict that it will not potentiate the BMP2 response.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We did not examine ALK6 here because an earlier report indicated that it was not expressed in LbT2 cells or adult mouse pituitary (Otsuka & Shimasaki 2002). However, more recent work shows that this receptor is in fact expressed (Suszko & Woodruff 2006), and we confirm this observation here. Given that ALK6 is more similar to ALK3 than ALK2, one would predict that it will not potentiate the BMP2 response.…”
Section: Discussionsupporting
confidence: 85%
“…7). One report indicated no expression of ALK6 in LbT2 cells or mouse pituitary (Otsuka & Shimasaki 2002), whereas more recent work (Suszko & Woodruff 2006) showed that it is expressed at low levels and our data are consistent with the latter report (Fig. 7).…”
Section: Bmp Receptors and Receptor-regulated Smads Are Expressed In supporting
confidence: 93%
“…Regulation of a specific transduction pathway through the availability of ligands and receptors is an established concept. In this context, Suszko and Woodruff [29] have demonstrated that receptor bioavailability would dictate the specificity of TGF-β action in rat pituitary gonadotropic cells. Therefore, the effects of TGF-β1 would depend on the balance between ALK1 and ALK5 in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…BMP4 is proteolytically activated by furin (15); however, BMP ligands do not regulate furin expression in mouse pituitary gonadotrope cells that express both BMP type I and type II receptors (27). Although it has been demonstrated that TGF␤1 can regulate furin gene expression in rat synoviocytes (28), this ligand cannot regulate furin mRNA in mouse pituitary gonadotrope cells because L␤T2 cells lack endogenous TGF␤ type II receptor and therefore are not responsive to TGF␤ ligand (29). This selective auto-regulation of furin by activin suggests that furin plays an important role in regulation of hormone biosynthesis and secretion from pituitary gonadotrope cells.…”
Section: Discussionmentioning
confidence: 99%